2014
DOI: 10.1111/jop.12211
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in AKT1 gene were associated with risk and survival of OSCC in Chinese Han Population

Abstract: Our results indicated that rs1130214 and rs3803300 were related to OSCC susceptibility in Chinese Han Population. In addition, rs3730358 might be associated with progression-free survival time of OSCC patients, suggesting that this SNP could be a potential prognosis marker for OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…TT p=0.008 [19] rs3093816 (Cyclin H) TC p<0.0001 ; CC p<0.0001 rs1800734 (hMLH1) GG p=0.006 [47] rs14133 (CRYAB) GG p=0.0002 [33] rs1130214 (AKT1) GT+TT p=0.006 [48] rs1412115 (Neuropilin-1) AG p=0.036 ; AG+GG p=0.042 [34] Analysis of SNPs via high throughput genomic analysis as reported in genome-wide association studies (GWAS) and next generation sequencing have emerged as a powerful approach to identify susceptibility loci enabling information on thousands of SNPs simultaneously. These platforms generally use smaller samples and are rather expensive and need to be validated in larger samples using alternative technology including nucleotide sequencing and Real-time PCR [17].…”
mentioning
confidence: 99%
“…TT p=0.008 [19] rs3093816 (Cyclin H) TC p<0.0001 ; CC p<0.0001 rs1800734 (hMLH1) GG p=0.006 [47] rs14133 (CRYAB) GG p=0.0002 [33] rs1130214 (AKT1) GT+TT p=0.006 [48] rs1412115 (Neuropilin-1) AG p=0.036 ; AG+GG p=0.042 [34] Analysis of SNPs via high throughput genomic analysis as reported in genome-wide association studies (GWAS) and next generation sequencing have emerged as a powerful approach to identify susceptibility loci enabling information on thousands of SNPs simultaneously. These platforms generally use smaller samples and are rather expensive and need to be validated in larger samples using alternative technology including nucleotide sequencing and Real-time PCR [17].…”
mentioning
confidence: 99%
“…This result was then verified by the same Korea group in 814 NSCLC patients with pathologic stages I, II, or IIIA who underwent curative surgical resection32. Wang Y et al 8. from China also indicated that variant genotypes AG and GG of AKT1:rs3803300, especially the GG genotype, showed a strong association with higher Oral squamous cell carcinoma (OSCC) susceptibility than the wild-type genotype AA, but they did not find any association between OSCC progression and genotype distribution of this SNP.…”
Section: Discussionmentioning
confidence: 75%
“…Several literatures have been reported that genetic variations in this pathway are associated with clinical outcomes, invasion property, drug resistance to chemotherapy and treatment complications, including head and neck squamous cell carcinoma, esophageal cancer, cervical cancer, gastric cancer, colorectal carcinoma, lung cancer and bladder cancer567891011121314151617. Although the involvement of this signaling pathway in the development and invasion of NPC have been addressed in many literatures41819202122, the clinical significance of genetic variations in this pathway remains unclear in NPC.…”
mentioning
confidence: 99%
“…Andreassen et al (2013) obtained negative results upon investigating the association of seven AKT1 SNPs (excluding rs1130214, rs3730358, and rs2494732) with the progression of testicular germ cell tumors in a large population of Norwegian-Swedish patients. rs3730358 and rs2494732 were also not related to the pathogenesis of oral squamous cell carcinoma in Chinese people (Wang et al, 2015). However, a population-based case-control study including The sequence of SNP loci is in the order of rs1130214, rs3730358, and rs2494732.…”
Section: Discussionmentioning
confidence: 92%
“…For example, rs2494750 in AKT1 showed significantly altered risk for PC-specific mortality (Karyadi et al, 2015). Polymorphisms rs3803300, rs1130214, and rs2494732 in AKT1 were significantly associated with the survival of patients in the early stage of non-small cell lung cancer (Kim et al, 2012), whereas polymorphisms rs1130214 and rs3803300 were related to susceptibility to oral squamous cell carcinoma (Wang et al, 2015). However, there is still no systematic research about the association between SNPs in AKT1 and the risk of development of PC.…”
Section: Introductionmentioning
confidence: 99%